Therapeutic Success of Rifaximin for Clostridium difficile Infection Refractory to Metronidazole and Vancomycin - George Tannous; Guy Neff; Nyingi Kemmer (Case Reports in Gastroenterology, 2010)
We report the case of a 46-year-old white male with confirmed Clostridium difficile infection for >4 weeks after fluoroquinolone therapy. The patient received two courses of metronidazole 500 mg three times daily (t.i.d.) during which time diarrhea resolved; however, symptoms recurred 14–15 days after treatment termination. He received a 2-week course of vancomycin 125 mg four times daily, with symptoms recurring 10 days after treatment conclusion. The patient then received a pulsed tapering schedule of vancomycin with adjunctive Saccharomyces boulardii. Diarrhea recurred 12 days after treatment completion. He received rifaximin 400 mg t.i.d. while hospitalized for diarrhea-associated complications. Symptoms resolved within 24 h. The patient received a 4-week regimen of rifaximin 400 mg orally t.i.d. after discharge. No further episodes of diarrhea were reported within 6 months after treatment termination. The present case supports the potential benefit of rifaximin for the treatment of recurrent Clostridium difficile infection.